ELECTRON MICROPROBE ANALYSIS OF RED PAINTED AND SLIPPED CERAMICS FROM CHOCOLA, GUATEMALA – AN INITIAL INVESTIGATION OF THE PIGMENTS AND METHODS OF APPLICATION. (2011) - Webb, Karen; Faber, Eddy; Weeks, Lloyd
No abstract available